Spectroscopy with Polarization Controlled Entangled Photons for Detecting Orbital Excitation in Solids - P, Munkhbaatar; D, Ulam-Orgikh; J, Vanchinkhuu (Scientific transaction of the National University of Mongolia. Physics, 2022)
We propose an excitation-probe measurement method utilizing entangled photon pulses. The excitation-probe signal is dominated by stimulated Raman scattering as well as two-photon absorption when the time delay between the excitation pulse and the probe pulse is shorter than the pulse duration. This paper demonstrates that the two-photon-absorption signal can be suppressed when the photons of the pulses are entangled. The stimulated Raman scattering signal can be composed of many peaks distributed over broad photon energies owing to the transitions between numerous quantum states in complex materials. We also show that the desired peaks among the many peaks can be selected by controlling the thickness of the nonlinear crystal, the pump pulse center frequency, and the polarization of the excitation pulse and probe pulse.